From "best practice" to "best fit": A framework for designing and analyzing pluralistic agricultural advisory services - Birner, Regina; Davis, Kristin E.; Pender, John L.; Nkonya, Ephraim M.; Anandajayasekeram, Ponniah; Ekboir, Javier; Mbabu, Adiel; Spielman, David J.; Horna, Daniela; Benin, Samuel; Kisamba-Mugerwa, Wilberforce (International Food Policy Research Institute, 2006)
Agricultural advisory services play an important role in supporting the use of the agricultural sector as an engine of pro-poor growth and enabling small farmers to meet new challenges, such as accessing export markets, adopting environmentally sustainable production techniques, and coping with HIV/AIDS and other health challenges that affect agriculture...There is now renewed interest in agricultural advisory services in many countries.... The questions under debate include: What should be the roles of the public sector, private sector, and civil society? How can we ensure that agricultural advisory services are demand-driven and meet the diverse information needs of farmers? How can advisory services be made efficient and financially sustainable? How can we ensure that female farmers, the poor, and other marginalized groups have access to agricultural advisory services?--Authors' Summary